PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MENGGUNAKAN MEDIA VIDEO DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Ira Rahayu; Gumilar, Rendra; Srigustini, Astri (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study focuses on finding out the low problem-solving ability of students in economics subjects. The purpose of the research is to determine the improvement of students' problem-solving skills through a problem-based learning model using video media. Using a quantitative approach with the Quasi Experiment method. The population in the study was all students of class XI IPS SMAN 8 Tasikmalaya as many as 215 students, the sampling technique used purposive sampling with an experimental class of 36 people using a problem-based learning model and a control class using another model. The results of the study show that there is an influence of the problem-based learning model using video media in improving problem-solving skills, where Ha is accepted if the value of sig (2-tailed)<0.005 and based on the research the value of sig.2(-tailed is 0.000<0.005. The average score of the experimental class is higher than that of the control class, therefore it is concluded in this study that the problem-based learning model using video media can improve students' problem-solving skills. Keywords: Problem solving skills, Problem based learning, Video